Comparison of the Results of SPR Analysis of Antigen-antibody Interactions Performed Using Optical Biosensors Biacore X-100 (“Cytiva”, USA) and MI-S200D (“Inter-Bio”, China) - Gnedenko, O.V.; Mezentsev, Y.V.; Yablokov, E.O.; Kaluzhskiy, L.A.; Ershov, P.V.; Gilep, A.A.; Ivanov, A.S. (Biomedical Chemistry: Research and Methods, 2025)
Limited availability of Western scientific equipment, explains a growing need to switch to using scientific instruments made in China. This is especially true in the case of optical biosensors operating on the surface plasmon resonance (SPR) effect. However, comparability of experimental data obtained using Western and Chinese biosensors has not been investigated yet. In this work we have comparedresults of SPR analysis of the kinetics and affinity of interaction of IgG2a and IgG1 antibodies with protein A. Two biosensos Biacore X-100 (“Cytiva”, USA) and MI-S200D (“Inter-Bio”, China) have been used. It was shown that the values of the association rate constants obtained on both devices for two antibodies were close within one order of magnitude. For IgG1 antibodies, the dissociation rate constants were almost identical. Both devices provide high-quality data that are well described by a simple 1:1 model (Langmuir binding).